Analysis of student's statistical thinking ability in understanding the statistical data - Masjudin, M; Muzaki, A; Abidin, Z; Ariyanti, I A P (Journal of physics. Conference series, 2020)
The purpose of this research is to describe the student's statistical thinking ability in understanding statistical data. The statistical thinking consists of the following four indicators: (a) ability to describe data; (b) ability to organize and reduce data; (c) ability to represent data; and (d) ability to analyse and interpret data. This research uses a qualitative approach with a phenomenological method. Subject in this research were eighth grade students of SMP Negeri 3 Lingsar. Data collection techniques by providing evaluation tests statistical thinking abilities and interviews. The results of this research showed that 4.2% of students had high statistical thinking ability, 25% of students had medium statistical ability, and 70.8% of students had low statistical thinking ability. So that, can be concluded the statistical thinking ability of students is in the low category. Student achievement in each indicator of statistical thinking ability is detailed as follows: (a) students ability to describe data is in the medium category; (b) students ability to organize and reduce is in the low category; (c) students' ability to represent data is in the medium category; and (d) Students' ability to analyse and interpret data is in the low category.